Skin-patch delivered subunit vaccine induces broadly neutralising antibodies against SARS-CoV-2 variants of concern. Issue 34 (12th August 2022) - McMillan, Christopher L.D.; Amarilla, Alberto A.; Modhiran, Naphak; Choo, Jovin J.Y.; Azuar, Armira; Honeyman, Kate E.; Khromykh, Alexander A.; Young, Paul R.; Watterson, Daniel; Muller, David A.
Abstract: The ongoing SARS-CoV-2 pandemic continues to pose an enormous health challenge globally. The ongoing emergence of variants of concern has resulted in decreased vaccine efficacy necessitating booster immunizations. This was particularly highlighted by the recent emergence of the Omicron variant, which contains over 30 mutations in the spike protein and quickly became the dominant viral strain in global circulation. We previously demonstrated that delivery of a SARS-CoV-2 subunit vaccine via a high-density microarray patch (HD-MAP) induced potent immunity resulting in robust protection from SARS-CoV-2 challenge in mice. Here we show that serum from HD-MAP immunized animals maintained potent neutralisation against all variants tested, including Delta and Omicron. These findings highlight the advantages of HD-MAP vaccine delivery in inducing high levels of neutralising antibodies and demonstrates its potential at providing protection from emerging viral variants.